Charging strategies for economic operations of electric vehicles in commercial applications. (March 2017) - Schücking, Maximilian; Jochem, Patrick; Fichtner, Wolf; Wollersheim, Olaf; Stella, Kevin
Highlights: Five different charging strategies for two e-mobility applications are presented. Charging strategies can be characterized with five key performance indicators. Predictable mobility patterns allow for individual charging strategy adaptation. Charging curves and energy consumption are the core inputs for charging strategies. A mix of charging levels allows a high mileage while limiting battery ageing. Abstract: When substituting conventional with electric vehicles (EV) a high annual mileage is desirable from an environmental as well as an economic perspective. However, there are still significant technological limitations that need to be taken into consideration. This study presents and discusses five different charging strategies for two mobility applications executed during an early stage long-term field test from 2013 to 2015 in Germany, which main objective was to increase the utilization within the existing technological restrictions. During the field test seven EV drove more than 450, 000 km. For four out of five presented charging strategies the inclusion of DC fast charging is indispensable. Based on the empirical evidence five key performance indicators (KPI) are developed. These indicators give recommendations to economically deploy EV in commercial fleets. The results demonstrate that the more predictable the underlying mobility demand and the more technical information is available the better the charging strategies can be defined. Furthermore, the results indicate that a prudent mix of conventional and DC fast charging allows a high annual mileage while at the same time limiting avoidable harmful effects on the battery.